Study of Medicinal Plants and Variety of Medicines Which Are Mentioned in Segaraja Segaram Jaffna Siddha Text Book - Sathyaseelan, V.; Thushyanthy, A. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
Indigenous system consists of Siddha, Ayurveda, and Unani medicines. In Siddha system not only for the herbal preparation but also most of the preparations are herbomineral preparations. Different texts are mentioned in siddha. But the objective of the study is to find out medicinal plants and medicines mentioned in Jaffna siddha text, Segaraja Segara Vaidyam. In this book there are several medicinal methods prepared from medicinal plants appeared. Totally 327 medicinal plants are mentioned for the preparation of siddha medicine. A total of 327 medicinal plants species belongs to 82 families were identified. Among the identified species 48 plants are belongs to the family of Leguminosae. Out of 327 medicinal plants (37) plants are mentioned in synonyms (unusual names). 18 plants were identified as poisonous. Accordingto the siddha pharmacodynamics (146) plants arebitter, (63) in sweet, (78) in pungent, (74) in astringent and (7) sour in taste. According to the Potency out of 327 species, (71.25%) of plants are hot in potency and (28.74%) plants cold in potency.Post digestive stage of Pirivu, (24.15%) plants are sweets, and (75.84%) are pungent. According to the pharmacological action significant amount of the plants are contain Diuretic action (60plants), Carminative (46), Alterative (35). According to the parts used in medicinal plants, roots are (160), leaves (88), bark (30), whole plant (8), seeds (37), fruits (13), flower (13), dry fruit (18) and resin (3). The following species are only mentioned in the Jaffna Siddha text book namely,Azima tetracantha, Erythroxylum monogynum, Hugonia mystax, Pisonia aculeate, Cappari saphylla, and Scutia indica. All 327 medicinal plants are mention in the Segaraja Segaram as well as internal and external medicine. 25 variety of medicine are mentioned. Out of 25, 15 types are internal and 10 types are external medicine. Significantnumbers of medicines are mentioned in decoctions form (110).
Keywords: Medicinal plants; Medicines; Segaraja Segaram siddha text book